Ototoxicity-induced hearing loss and quality of life in survivors of paediatric cancer. (November 2020) - Rajput, Kaukab; Edwards, Lindsey; Brock, Penelope; Abiodun, Anne; Simpkin, Phillippa; Al-Malky, Ghada
Abstract: Introduction: Hearing loss is a permanent and debilitating side-effect of a range of interventions commonly used in the treatment of childhood cancers, primarily ototoxic medications such as cisplatin. The purpose of this study was to examine the impact of hearing loss, in a population already at risk of reduced quality of life due to the cancer and treatment-related factors. Methods: This study used a questionnaire specifically designed to tap issues relevant to children with hearing loss, the Paediatric Audiology Quality of Life questionnaire (PAQL). Parents of 78 children treated for a wide range of solid tumours and leukaemias completed the PAQL, 41 of whom had sensorineural hearing loss as a result of the cancer treatment. Results: Significant differences between those children with hearing loss and those whose hearing remained normal were found on all four scales of the questionnaire. Children affected by ototoxicity were rated as having poorer quality of life in terms of their ability to communicate with family and peers, their independence, interactions with peers and emotional well-being. Conclusion: These results highlight the impact of acquired hearing loss and reinforce the importance of assessing quality of life with a measure capable of tapping the issues of consequence to the population under investigation. They also have implications for the clinical management of children during and following treatment for a wide range of cancers: medically, audiologically, psychologically and educationally.